2015
DOI: 10.5194/hess-19-1401-2015
|View full text |Cite
|
Sign up to set email alerts
|

Assessing downstream flood impacts due to a potential GLOF from Imja Tsho in Nepal

Abstract: Abstract. Glacial-dominated areas pose unique challenges to downstream communities in adapting to recent and continuing global climate change, including increased threats of glacial lake outburst floods (GLOFs) that can increase risk due to flooding of downstream communities and cause substantial impacts on regional social, environmental and economic systems. The Imja glacial lake (or Imja Tsho) in Nepal, which has the potential to generate a GLOF, was studied using a two-dimensional debris-flow inundation mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 32 publications
1
65
1
1
Order By: Relevance
“…Everest (Figure 1). Several communities exist in the region and rely on agriculture and tourism for their income [18]. In this study, we focus on the community of Dingboche, which is approximately 7 km downstream from Imja Lake.…”
Section: Study Areamentioning
confidence: 99%
See 3 more Smart Citations
“…Everest (Figure 1). Several communities exist in the region and rely on agriculture and tourism for their income [18]. In this study, we focus on the community of Dingboche, which is approximately 7 km downstream from Imja Lake.…”
Section: Study Areamentioning
confidence: 99%
“…Rounce et al [23], found that Imja Lake was of moderate risk at that time due to its low hazard ranking and high downstream impact potential, but that the hazard and risk of the lake will likely increase over the next few decades if the lake continues to grow at its current rate. Despite the disagreement over the danger posed by Imja Lake, researchers have conducted numerous studies to understand how a GLOF from the lake would affect areas downstream [2,18,23]. Other studies of the lake have also focused on lake characteristics [25], moraine and glacier characteristics [31], and melting of source glaciers [32].…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…One-dimensional models based on the St. Venant equations have been used to model the downstream flood wave propagation of a GLOF, e.g., Klimes et al (2013), who used HEC-RAS (USACE, 2010) to reproduce the 2010 GLOF from Lake 513 in Peru, Cenderelli and Wohl (2003), who used HEC-RAS to reproduce steady-state aspects of GLOFs in the Khumbu region of Nepal, Byers et al (2013), who used HEC-RAS to model a potential GLOF from Lake 464 in the Hongu valley of Nepal, Meon and Schwarz (1993), who used DAMBRK (Fread, 1988) to model a potential GLOF in the Arun valley of Nepal, and Bajracharya et al (2007), who used FLDWAV (NWS, 1998 to model a potential GLOF from Imja Lake in Nepal. Two-dimensional SWE models are often used to model downstream impacts of GLOFs, e.g., Worni et al (2012), who used BASEMENT to model flooding from a GLOF at Shako Cho Lake in India, Schneider et al (2014), who used RAMMS to model debris flow from an overtopping wave at Lake 513 in Peru, Somos-Valenzuela et al (2015), who used FLO2D to model downstream inundation from a potential GLOF at Imja Lake in Nepal, and Mergili et al (2011), who used RAMMS and FLO2D to simulate flooding from Lake Khavraz in Tajikistan. FLO2D (2012) is used here to simulate the downstream inundation.…”
Section: Introduction To Glacial Lake Hazard Process Chain Modelingmentioning
confidence: 99%